2023
DOI: 10.3390/en16020832
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Design Method for the Lighting Environment of a Library Building Based on Building Performance Evaluation

Abstract: The lighting conditions of a library directly affect the users’ spatial experience, with glass curtain walls being widely used in the design of library skins. Although glass curtain walls have been extensively adopted, they increase indoor sun exposure and glare. Considering sunlight duration and radiation as the design basis, this study employs the Rhino and Grasshopper parametric platforms to parametrically design a library with a dynamic shading skin. Specifically, our design utilizes modular shading compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Considerations like size, orientation, energy efficiency, and technological advancements play crucial roles in modern library architecture. Other findings include that of Liu, Han, Yan, and Ren (2023) who found that factors influencing library design include sunlight duration, radiation, and dynamic shading components. Parametric design methods optimize lighting performance based on these factors for enhanced user experience.…”
Section: Resultsmentioning
confidence: 96%
“…Considerations like size, orientation, energy efficiency, and technological advancements play crucial roles in modern library architecture. Other findings include that of Liu, Han, Yan, and Ren (2023) who found that factors influencing library design include sunlight duration, radiation, and dynamic shading components. Parametric design methods optimize lighting performance based on these factors for enhanced user experience.…”
Section: Resultsmentioning
confidence: 96%
“…1) Designing with high-precision simulation tools has become a prevalent trend in digital assisted lighting design. Although along with the prosperous development in 3D modelling after 2018, there has been an increase in the use of 3D modelling software, for lighting design research [8]- [11]. Here still requires a more dynamic bilateral information exchange between the physical asset and the virtual asset to provide detailed environment and boundary parameter inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Even multi-purpose simulation tools occupied half the popularity in previous studies, but they were mainly geared toward a specific use (thermal, energy and lighting simulation) without information exchange within all modules of a simulation system, and individual case studies required multiple instantiation efforts. Along with the prosperous development in 3D modelling after 2018, there has been an increase in the use of 3D modeling software, specifically Rhino and its-based plugins, for lighting design research [8]- [11]. These plugins are based on the RADIANCE engine and have similar features that enhance the understanding of how the built environment interacts with the surrounding climate and enable the optimization of lighting design for energy efficiency, environmental sustainability, and human factors such as visual comfort, circadian rhythm, and well-being.…”
Section: Simulation Tools and Associated Strategiesmentioning
confidence: 99%
“…By altering WWR, the amount of daylight entering the interior can be adjusted, thus affecting indoor illuminance [20]. Increasing facade shading can reduce the amount of daylight entering the interior, thereby lowering the DGP value [21]. Ensuring sufficient indoor light when adjusting both windows and blinds as necessary can prevent overheating while conserving energy [22].…”
Section: Introductionmentioning
confidence: 99%